Books in Motion in Early Modern Europe
XIII, 305 p. 27 illus.
Keywords: ‘This rich crop of new empirical research in book history focuses especially on the movement of books through markets and networks of users. Eleven case studies span an impressive variety of analytical techniques, primary sources, and contexts.’ — Ann M. Blair, Henry Charles Lea Professor of History, Harvard University, USA ‘This book contributes significantly to a spatial turn in the history of the book. Its contributors identify innovative means of combining the study of the life-cycle of books with their mode and compass of transmission. The collection notably extends our understanding of the social history of knowledge.’ — James Raven, Professor of Modern History, University of Essex, UK This book presents and explores a challenging new approach in book history. It offers a coherent volume of thirteen chapters in the field of early modern book history covering a wide range of topics and it is written by renowned scholars inthe field. The rationale and content of this volume will revitalize the theoretical and methodological debate in book history. The book will be of interest to scholars and students in the field of early modern book history as well as in a range of other disciplines. It offers book historians an innovative methodological approach on the life cycle of books in and outside Europe. It is also highly relevant for social-economic and cultural historians because of the focus on the commercial, legal, spatial, material and social aspects of book culture. Scholars that are interested in the history of science, ideas and news will find several chapters dedicated to the production, circulation and consumption of knowledge and news media. .